The Lantern Bearers - Sutcliff, Rosemary (Oxford University Press, 1979)
The last of the Roman army have set sail and left Britain forever. They have abandoned the country to civil war and the threat of Saxon invasion. When his home and all he loves are destroyed, Aquila endures years of torment. He fights to bring some meaning back into his life, and with it the hope of revenge...
Keywords: Juvenile literature-Historical-Roman Britain-Fiction